GAMBARAN PENGETAHUAN PASIEN TUBERKULOSIS PARU DALAM PENCEGAHAN PENULARAN INFEKSI DI RUANGAN INTERNIS RUMAH SAKIT SANTA ELISABETH MEDAN - Jolly Wilthon Panjaitan; Nagoklan Simbolon (Elisabeth Health Jurnal, 2017)
Pulmonary Tuberculosis is an infectious disease that attacks the lung parenchyma, caused by mycobacterium tuberculosis. This disease can also spread to other body parts such as meninges, kidneys, bones and lymph nodes of pulmonary TB is a big problem for developing countries including Indonesia As most developing countries do. Almost all adult residents have been infected by TB bacilli in easy times, since most pulmonary TB disease in this country is caused by bacilli that undergo reactivity Goals : To know the description of the patient's knowledge of TBC Lung prevention transmission of pulmonary tuberculosis infection in the internal room At Santa Elisabeth Hospital Medan. Method: type of rancanagn case study used is descriptive number of subjects is as much as 9 0rang data collection in the form of questionnaires after that done scoring data is presented in the form of tables and distribution frequency Results: From the case study the frequency distribution of respondents based on the use of the questionnaire. From the case study conducted (seen in table 4.1) that more male sex is 9 people (100%) and female 0 (0%). From this case study, the result is good.. Conclusion: Based on the results of the case studies described above, the authors conclude the case study results that the level of education greatly influences the patient's knowledge in preventing transmission of TB disease. It is evident that the level of education of the upperand upper-secondary patients with the highest proportion of case studies ( 55,5%) know the mode of transmission of infection prevention.